2011
DOI: 10.1083/jcb.201012179
|View full text |Cite
|
Sign up to set email alerts
|

SLAIN2 links microtubule plus end–tracking proteins and controls microtubule growth in interphase

Abstract: SLAIN2’s interactions with multiple different microtubule plus end–tracking proteins stimulate processive microtubule polymerization and ensure proper microtubule organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
133
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 48 publications
13
133
4
Order By: Relevance
“…Because Centralspindlin is a heterotetrameric complex (Mishima et al, 2002) and forms higher-order clusters that are important for its function (Hutterer, Glotzer, and Mishima, 2009), it is possible that multiple SxIP motifs within Centralspindlin clusters may facilitate its association with EBs in cells. Indeed, the presence of multiple SxIP motifs that mediate binding to EBs has been noted in other +TIP proteins (Applewhite et al, 2010;Buey et al, 2012;Honnappa et al, 2009;van der Vaart et al, 2011). Interestingly, we found that although mutation of the Mgc SxIP motif strongly reduces the ability of Mgc to track with EB3, the mutant Mgc still affected the EB3 run time along MTs.…”
Section: Discussionsupporting
confidence: 55%
“…Because Centralspindlin is a heterotetrameric complex (Mishima et al, 2002) and forms higher-order clusters that are important for its function (Hutterer, Glotzer, and Mishima, 2009), it is possible that multiple SxIP motifs within Centralspindlin clusters may facilitate its association with EBs in cells. Indeed, the presence of multiple SxIP motifs that mediate binding to EBs has been noted in other +TIP proteins (Applewhite et al, 2010;Buey et al, 2012;Honnappa et al, 2009;van der Vaart et al, 2011). Interestingly, we found that although mutation of the Mgc SxIP motif strongly reduces the ability of Mgc to track with EB3, the mutant Mgc still affected the EB3 run time along MTs.…”
Section: Discussionsupporting
confidence: 55%
“…Our past (15) and present results support the emerging concept that serine and threonine phosphorylation in the SXIP flanking regions is used in cells to destabilize the SXIP-EB complex and probably also the interaction with microtubules through an electrostatic repulsion effect. Prominent examples of ϩTIPs that are regulated by phosphorylation within their MtLS sequences include MCAK (15), CLASP (16), APC (7), and SLAIN2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently found that multiple SXIP motifs can act in concert to enhance microtubule tip localization in cells (15,21,40). To assess the effect of multiple SXIP motifs, we investigated the S. cerevisiae ϩTIP Ipl1p (24, 25), which contains two consecutive SXIP motifs (Fig.…”
Section: Binding Of Different Sxip-containing ϩTip Fragments To Ebs Amentioning
confidence: 99%
“…Family members utilize characteristic domains to localize to MT plus-ends and promote MT polymerization. XMAP215 family members have a conserved C-terminal domain that binds SLAIN2 (H. sapiens)/Sentin (D. melanogaster), which confers EB1-dependent MT plus-end localization (33,34). EB1 fenestrates the MT lattice, binding between four tubulin heterodimers where it recognizes tubulin in a GTP hydrolysis transition/post-hydrolysis state mimicked by the GTP analog GTP␥S (58 -60).…”
Section: Discussionmentioning
confidence: 99%